From Party Autonomy to Algorithmic Autonomy: Reconstructing the Principle of Freedom of Contract in Artificial Intelligence-Generated Contracts - Chandera Halim (Rechtsvinding, 2026)
The increasing use of artificial intelligence in drafting, reviewing, and negotiating contracts challenges the traditional conception of freedom of contract, which is founded on the autonomous will, informed consent, and equal bargaining position of the contracting parties. This study examines whether contracts generated or substantially shaped by artificial intelligence can still be regarded as genuine expressions of party autonomy and seeks to reconstruct the principle of freedom of contract in response to the emergence of algorithmic autonomy. The research employs a normative legal method using statutory, conceptual, and comparative approaches, supported by an analysis of contract law doctrines, electronic transaction regulations, and contemporary principles of artificial intelligence governance. The study finds that an artificial intelligence-generated contract may remain legally valid when the system functions merely as an instrument acting within parameters determined by legally competent parties. Nevertheless, formal consent alone is insufficient to demonstrate genuine contractual freedom when parties do not understand the operation of the artificial intelligence system, the origin of the generated clauses, or the legal risks arising from algorithmic errors, bias, and unequal technological capacity. The study proposes a reconstructed model of freedom of contract based on meaningful human control, informed algorithmic consent, transparency regarding the use of artificial intelligence, the ability to review and modify generated clauses, and clear attribution of responsibility for technological errors. It concludes that algorithmic autonomy should not replace party autonomy but must remain subordinate to human intention, fairness, accountability, and the protection of contracting parties.